ABOUT SELF-EDUCATION AND ITS ROLE IN PERSONALITY DEVELOPMENT (American Journal of Research in Humanities and Social Sciences, 2023)
The article discusses independent education and its significance, aspects of the organization of independent education. Many aspects of independent learning and their positive impact on the level and quality of education are discussed.